Hatching Some Empirical Evidence: Minority Ownership Policy and the FCC's Incubator Program. Issue 3 (3rd July 2019) - Terry, Christopher; Carlson, Caitlin Ring
Abstract : Despite the ongoing legal and regulatory battle over media ownership policy, control of broadcast outlets among racial and ethnic minorities and women has remained at critically low levels. The Federal Communication Commission's latest proposal, an Incubator program, relies on the idea that new, small entities can be created by incentivizing existing media companies to foster new entrants in exchange for additional ownership consolidation at the local level. This article traces the FCC's efforts on minority ownership policy, examines relevant literature on the relationship between minority ownership and diversity, and reports empirical data regarding minority focused content production by a variety of ownership types to determine what ownership structures are currently producing minority focused content. The data suggest that the FCC has been correct to focus on smaller ownership structures. The article concludes with a proposal for the FCC to undertake to put stations in the hands of minority owners.